Comparison of Infra Orbital Nerve Outcome in Zygomaticomaxillary Complex Fractures Treated Surgically and Conservatively - Nahmeed Ullah, Nighat Khan, Jahangir Hammad, Nizam Ul Mulk, Anum Javed, Gul Khanda, Assad Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Zygomaticomaxillary complex fractures are second most common facial injuries. These fracture are managed either by open reduction with rigid fixation or conservatively. Objective: To compare infra orbital nerve outcome in zygomaticomaxillary complex fractures treated surgically and conservatively. Methodology: The current randomized controlled trial study was carried out at Oral and Maxillofacial Surgery Department, Sandeman Provincial Hospital/Bolan Medical College Quetta from 23/04/2018 to 22/10/2018 after the synopsis approval. Total sample size calculated was 100. 50 patients in Group-A were treated by open reduction and internal fixation technique and 50 patients in Group-B were managed conservatively without any intervention. All the data was recorded in a specialized proforma for this study. Data analysis was done by SPSS. Results: The overall mean age (SD) of the patient’s was 36.2±7.1 years. Most of the patients (n=64, 64.0%) were 31-45 years old. The male patients in our study were 65 (65.0%) whereas female participants were 35 (35.0%). For detection of mechanical threshold, the patients proportion with sensations at 3cm filament length was significantly lower in patients who underwent surgical treatment (78.0% vs. 100.0%; p-value<0.001) as compared to the participants managed conservatively. It was also lower significantly at 5cm and 7cm for Group-A in comparison to Group-B (p-value≤0.05). For detection of heat threshold, the patients proportion with sensation at 32°C was no different between Group-A and Group-B (p-value=0.529). However, proportion of patients with sensations at 35oC (64.0% vs. 100.0%; p-value<0.001) and 37oc (90.0% vs. 100.0%; p-value=0.022) was lower significantly in surgically treated patients. Pain threshold detection was significantly lower in patients who underwent surgical treatment (1.26±0.44 vs. 1.58±0.49; p-value<0.001) in comparison to conservative treatment. Conclusion: In patients with zygomaticomaxillary complex fractures, infra orbital nerve outcome was superior in patients managed conservatively than those treated with open reduction and internal fixation which advocates evading unnecessary intervention in such cases in future practice. Keywords: Zygomaticomaxillary Complex Fractures, Conservative Treatment, Infra Orbital Nerve